Estudo comparativo entre a Adidas e a Nike sob o enfoque do ambiente Lean : manufacturing e accounting - Silva, Roberta Cristina da; Silva, Tatiane Moraes da; Santos, Fernando de Almeida; Robles Junior, Antonio (Pontifícia Universidade Católica de São Paulo - PUC/SP, 2019)
This article is about the Lean Manufacturing concept. The current reality presents highly competitive markets and the incessant search of improvement of performance by the managers aiming at better profit margins and reduction of wastes. Such practices result in lower costs and better return on business. The delimitation of the study occurred by choosing two companies that occupy prominent positions in the sporting goods sector: Nike and Adidas. A comparative analysis between such companies, since there is the adoption of lean manufacturing only in Nike. The analysis with the financial statements of both companies showed better efficiency for the company with lean culture. Therefore, this article demonstrates positive results through the adoption of Lean Manufacturing in Lean Accounting as options and guidelines for the reduction of waste and better operational performance that result in better monetary outcomes for the organizations that decide to adopt lean manufacturing, the implementation of new business practices. Keywords: Lean thinking. Lean manufacturing. Accounting lean.

Este artigo trata dos conceitos de Lean Manufacturing ou Manufatura Enxuta e Lean Accounting ou Contabilidade Enxuta. A realidade atual apresenta mercados altamente competitivos e a busca incessante de melhoria de desempenho por parte dos gestores, visando melhores margens de lucro e redução de desperdícios. Tais práticas resultam, consequentemente, na diminuição de custos e em melhor retorno para os negócios. A delimitação do estudo ocorreu mediante a escolha de duas empresas que ocupam posições de destaque no setor de artigos esportivos: Nike e Adidas. Uma análise comparativa entre tais empresas, visto que há a adoção da fabricação enxuta apenas na Nike. A observação comparativa mediante os demonstrativos contábeis de ambas as empresas evidenciou melhor eficiência para a empresa com cultura lean. Portanto, o presente artigo consegue evidenciar resultados positivos por meio da adoção do Lean Manufacturing concomitantemente ao Lean Accountig como opções e diretrizes para a redução de desperdícios e melhor desempenho operacional que decorrem em resultados monetários melhores as organizaçãoes que decidem pela adoção a fabricação enxuta, com a implementação de novas práticas ao negócio.
The Adoption of Lean Manufacturing to Improve Performance a Comparative Study Adidas and Nike
Keywords: Lean manufacturing; Lean accounting; Lean thinking; Accounting lean; Pensamento enxuto